Model building to facilitate understanding of holliday junction and heteroduplex formation, and holliday junction resolution. - Selvarajah, Geeta; Selvarajah, Susila (Wiley, 2016)
Students frequently expressed difficulty in understanding the molecular mechanisms involved in chromosomal recombination. Therefore, we explored alternative methods for presenting the two concepts of the double-strand break model: Holliday junction and heteroduplex formation, and Holliday junction resolution. In addition to a lecture and computer-animated video, we included a model building activity using pipe cleaners. Biotechnology undergraduates (n = 108) used the model to simulate Holliday junction and heteroduplex formation, and Holliday junction resolution. Based on student perception, an average of 12.85 and 78.35% students claimed that they completely and partially understood the two concepts, respectively. A test conducted to ascertain their understanding about the two concepts showed that 66.1% of the students provided the correct response to the three multiple choice questions. A majority of the 108 students attributed the inclusion of model building to their better understanding of Holliday junction and heteroduplex formation, and Holliday junction resolution. This underlines the importance of incorporating model building, particularly in concepts that require spatial visualization.